Aplicación de las normas internacionales de información financiera (niif), para pymes en “Almacenes Multihogar” ubicado en la parroquia San Miguel, del cantón Salcedo, provincia de Cotopaxi , en el período del 01 de agosto al 31 de diciembre del 2013 - Guachamboza García, María Elizabeth (2015)
This research was developed in "ALMACENES MULTIHOGAR" with the end to implement the International Financial Reporting Standards (NIIF) for PYMES in the financial statements, given the need of the company so he can face various financial changes that occur nationwide. This required making a methodology focused on the process of implementing the NIIF for PYMES allowing know the activities that take place in different departments, using surveys and interviews with those who are part of the company getting results, since all the staff was willing to collaborate on the needs within the company. With the development of the assessment it was established if the respective search policies and procedures adopted by the company is given; in this paper we show the importance of the application of NIIF for PYMES in order to formulate and present a review of the results of the financial statements….